An application of generalized tanh function method for the sixth-order Boussinesq (sB) equation and (1+1) dimensional dispersive long wave equation - Demiray, Seyma Tuluce; Bulut, Hasan; Onargan, Gonca (Hikari Ltd., 2015)
In this paper, we present some exact solutions of the special sixth-order Boussinesq (sB) equation and (1+1) dimensional dispersive long wave equation (DLWE) by using generalized tanh function method. These equations can be transformed to nonlinear ordinary differential equations. Subsequently, generalized tanh method has been implemented to acquire the exact solutions of these equations and we acquire some new exact solutions such as multiple soliton-like solutions and triangular periodic solutions. Also, we draw 2D and 3D graphics of exact solutions for the special sixth-order Boussinesq (sB) equation and (1+1) dimensional DLWE by the help of programming language Mathematica. © 2014 Seyma Tuluce Demiray, Hasan Bulut and Gonca Onargan.
Keywords: (1+1) dimensional dispersive long wave equation; Generalized tanh function method; The special sixth-order Boussinesq (sB) equation